Tasting the Little Scroll: A Sensory Analysis of Divine Interaction in Revelation 10.8-101. (September 2017) - Warren, Meredith J.C.
The ingestion of the scroll in Rev. 10.8-10 is a key element of how John experiences God's revelation and transmits it to others. Using sensory analysis, I propose that the scroll's ingestion represents a shared understanding of how the consumption of otherworldly food in narrative grants access to the divine realm and thereby transmits divine knowledge. The privacy of taste (as opposed to the shared senses of sight or hearing) suggests that participants in this kind of eating experience God in the most intimate way. The special way that John accesses these divine revelations – through consuming the little scroll – shows that he is granted privileged access to God's knowledge, which, when translated into visions, allows others to participate in this intimacy.